LanroNET, a non-interventional, prospective study to assess the resource utilization and cost of lanreotide autogel 120 mg in Polish patients with neuroendocrine tumors – results of interim analysis - Orlewska, Ewa; Bednarczuk, Tomasz; Kaminski, Grzegorz; Kos-Kudla, Beata; group, LanroNET study (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: To examine characteristics and treatment patterns of symptomatic neuroendocrine tumors (NETs) patients who received lanreotide Autogel 120 mg (ATG120) administered as part of routine clinical practice. Material and methods: Lanro-NET is a national, multicenter, non-interventional, observational study in the population of adult patients with symptomatic NETs treated with ATG120 for at least three months before inclusion. Data on demographic and clinical characteristics of the population, dosing interval regimen and aspects of administration were collected prospectively during 12 months. Costs were calculated from the perspective of public payer for the year 2014. Results: Fifty-two patients were enrolled in the study. Primary tumors were located predominantly in gastrointestinal tract (51.2%), all tumors were metastatic. The most commonly reported disease symptoms were flushing and diarrhea (55.8% of patients). 86% of patients had undergone surgery, chemotherapy and radioisotope therapy were used in 11.6% and 46.5% of patients, respectively. During the 12-months observation 12 (28%) patients received ATG120 at an extended dosing interval (> 4 weeks), the mean number of days between injections was 31.75 (SD 6.74). The cost of ATG12 was estimated at 4273.17 PLN patient/month. In all patients ATG120 was administered by nurse, 51.6% of injections in out-patient setting, 48.4% – in hospital. Conclusions : This study presents the current use of ATG120 in the population of Polish NETs patients in a realistic clinical settings. Finding that 28% of patients could be treated with extended dose intervals supports the potential for ATG120 of reducing treatment burden.